Potential of a Cladosporium cladosporioides strain for the control of Tetranychus urticae Koch (Acari: Tetranychidae) under laboratory conditions - Angie Gámez-Guzmán; Esperanza Torres-Rojas; Andreas Gaigl (Agronomía Colombiana, 2019)
The two spotted spider mite Tetranychus urticae is an important polyphagous pest worldwide. It is able to adapt to a wide variety of environments and has a high reproduction rate. In practice, farmers try to reduce losses by using synthetic acaricides. However, frequent and inadequate applications of acaricides have made this mite resistant to many active ingredients, creating the need to search for alternative control strategies. The aim of this research was to identify and to evaluate an indigenous strain of a fungus, which eliminated a T. urticae colony in a greenhouse. The isolated fungus was identified through a morphological and molecular characterization as Cladosporium cladosporioides. Thereafter, the mites were treated with five concentrations of C. cladosporioides conidia (2x104, 2x105, 2x106, 2x107, and 2x108 conidia ml-1) and a positive control (commercial Beauveria bassiana strain, 1x106 conidia ml-1). After 10 d, all treatments achieved at least 50% control; the concentrations 2x107 and 2x108 spores ml-1 controlled 73.3% and 81.7%, respectively, surpassing the commercial strain slightly (72.3%). TL50 ranged between 5 (2x108 spores ml-1) and 8 (2x104 spores ml-1) d, and LC50 was 1.95x106. The possible acaricidal effect of this strain on these mites is discussed.